Research on the efficiency of using solar tracker in urbanized conditions - Petryk, O.; Nazarenko, I.; Vasilyeva, E.; Kuzmenko, A.; Zhukov, R. (Energy and Automation, 2025)
In the context of rising energy prices and the need for energy independence, the development of renewable energy sources, in particular solar, is becoming particularly relevant. Solar power plants (SPPs) on the roofs of multi-story buildings are a promising solution for urban environments, where the area for ground-based installations is limited. To maximize electricity production from a limited area, it is critical to use technologies that increase system efficiency. Solar trackers, which automatically orient photovoltaic modules perpendicular to the sun's rays, are one of the most effective tools for achieving this goal. The main objective of this study is to analyze the technical and economic feasibility of implementing different types of solar trackers for a solar power plant located on the roof of a typical nine-story building. The objectives are:• to conduct a comparative analysis of single-axis (HSAT, VSAT, tilted axis) and dual-axis trackers;performing technical generation calculations and assessing the impact of key factors such as spatial constraints, shading and temperature;• assessing economic feasibility, taking into account initial investments and payback;• providing sound recommendations for two specific locations in Ukraine: Zaporizhia (south) and Ivano-Frankivsk (west).Key words: photovoltaic module, solar tracker, single-axis trackers, temperature, insolation, multi-storey building